Opportunities to inform German residents about the possibility of skin cancer screening and to inform stakeholders to take appropriate actions: A qualitative approach - Steeb, Theresa; Wessely, Anja; Heppt, Markus; Erdmann, Michael; Klug, Stefanie J.; Berking, Carola (Cancer Medicine, 2023)
Background: The national skin cancer screening (SCS) was introduced in Germany in 2008. However, public awareness and participation rates remain low. There are no campaigns or target group–specific invitation strategies for SCS yet. Thus, our aim was to derive potential suggestions on how to best inform German residents about the possibility of SCS. Methods: Semi–structured, individual interviews with male and female German residents aged =35 years were conducted in Erlangen (Germany) to explore opportunities on raising awareness of SCS. Interviews were audiotaped, transcribed verbatim, and analyzed using qualitative content analysis. Results: Overall, 39 persons were interviewed. About 79.5% (31/39) had already undergone at least one SCS. Numerous opportunities to raise awareness of the possibility of SCS were suggested which were categorized into three main topics: the role of public promotion, health–related caregivers, and health insurance. Similar themes were identified for inviting entitled persons to undergo SCS after 2 years. Furthermore, age–dependent communication approaches were proposed, that is, younger persons should be approached electronically, while the older generation should be targeted with traditional media like mail. Conclusions: The results of this project will inform stakeholders to take appropriate actions. The findings may contribute to increase participation rates in SCS and thus lead to earlier detection of skin cancer.
CRIS-Team WoS Importer:2023-05-12